Analiza vpliva razpokanosti na togost upogibno obremenjenega ojačanega betonskega nosilca z modelom razmazane razpoke - Bratina, Sebastjan (Gradbeni vestnik, 2018)
This paper presents a one-dimensional (1D) mechanical model for the analysis of the influence of cracking on the stiffness of reinforced concrete element under short-term static load. The Reissner geometrically non-linear planar beam theory is used to model each subcomponent of the beam. The bending stiffness of the tendon is neglected. The tangential slip between the tendon and concrete is fully accounted for, while the normal separation is not allowed. The non-linear material law of concrete, reinforcing and prestressing steel is considered. Cracking of concrete is accounted for using smeared crack model. In the numerical solution the mesh dependence is resolved by using the crack-band element, the dimension of which is related to the fracture energy of concrete. The validity of the presented mechanical model is verified on reinforced and prestressed concrete beam previously studied in literature. It is determined that the results of the present 1D model are well in line with the experimental results. The results are also qualitatively comparable with those obtained with significantly more complex 2D and 3D mechanical models.
Keywords: armirani beton; finite element method; metoda končnih elementov; natezna togost; prednapeti beton; prestressed concrete; razmazana razpoka; reinforced concretež; slip; smeared crack; tension stiffening; zdrs